Cyberstalking: Kejahatan Terhadap Perlindungan Data Pribadi Sebagai Pemicu Tindak Pidana - Amelia Putri Anisah; Eko Nurisman (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
The rapid development is marked by changes in telecommunications technology and computer technology. Technological sophistication gives rise to various kinds of crimes aimed at the virtual world community, one form of crime that occurs is cyberstalking. From this phenomenon, it is necessary to describe several arrangements that serve as the basis for tackling the rapid rate of cyberstalking. This research employs a normative judicial approach based on legal data gleaned from research sources. The primary and secondary legal information used in this research are both primary and secondary. The law number contains the majority of the legal information. 1. Amendments to the Information and Electronic Transactions Law No. 11 of 2008 (UU ITE) No. 19 of 2016 on Information and Electronic Transactions (UU ITE). Obtain secondary legal materials through library research, such as books, legal publications, the Internet, and expert opinion. The results of this study show that due to the rapid development of technology, many crimes stem from technological sophistication, including those related to cyberstalking, so it requires a special regulation that regulates cyberstalking, while there is no special regulation in tackling cyberstalking crimes. Regulations related to cyberstalking are still adopting the provisions of the ITE Law No. 19 of 2016 amendments to the ITE Law No. 11 of 2008.